Achieving Sustained Performance in the Nigerian Oil and Gas Sector despite Exchange Rate Fluctuations: A VAR Approach - Isibor, Areghan A.; Kehinde, Adetiloye A.; Felicia, Olokoyo O.; Tolulope, Adesina F.; Victoria, Akinjare A.; Mercy, Udume E. (International Journal of Energy Economics and Policy, 2022)
The issue of sustaining performance in the Nigerian oil and gas sector is one issue that is of concern to the present government of President Muhammadu Buhari and is in line with the UN’s Sustainable Development Goal (SDG) 7 of Clean Energy. The study examined the relationship between exchange rate fluctuations and Nigerian oil and gas sector performance with respect to achieving a sustainable economic growth. The three models used for the study are OBOP = f(OILE, OILI); OILO = f(EXR); and OILE = f(EXR). Secondary data were gathered and analyzed using the vector autoregression (VAR). The unit root test showed that all the variables were stationary at first difference while the Johansen cointegration proved the presence of a long run relationship among the variables in the model. The VAR result revealed that both oil export (OILE(-1)) and oil imports (OILI(-1)) were significant both positively and negatively respectively with overall balance of payments (OBOP). Also, nominal exchange rate (EXR(-1)) was positively significant with OILE while EXR(-1) was negatively significant with OILO. The study therefore recommended amongst others that more refineries should be built in Nigeria, so more products are extracted from crude oil and can be exported to boost revenue.